Filsafat Pendidikan Islam Bernapaskan Toleransi: Membaca Kembali Pemikiran Gus Dur untuk Generasi Baru - Sihono, Ridwan Faqih; Havid Nur Solikhin; Mahmud Arif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to explore the philosophy of Islamic education grounded in tolerance by revisiting the influential ideas of Gus Dur and assessing their significance for the younger generation in contemporary society. Adopting a qualitative descriptive approach through document analysis, in-depth interviews, and thematic interpretation, the research highlights that values such as tolerance, humanism, intellectual freedom, and respect for diversity are essential foundations for shaping modern Islamic education. The findings indicate that incorporating these principles into educational curricula not only enriches the learning experience but also strengthens inclusive and participatory teaching practices, fostering an environment that encourages open dialogue, mutual understanding, and moderation. Furthermore, the study emphasizes that systematic integration of Gus Dur’s educational philosophy can contribute to the development of students’ critical thinking, ethical awareness, and social responsibility, ensuring that Islamic education remains relevant and responsive to contemporary societal challenges. Overall, the research concludes that implementing these values consistently is crucial for advancing a modern, tolerant, and pluralistic approach to Islamic education that benefits both individuals and society as a whole.